2013
DOI: 10.1155/2013/304290
|View full text |Cite
|
Sign up to set email alerts
|

The Ethanol Extract ofOsmanthus fragransFlowers Reduces Oxidative Stress and Allergic Airway Inflammation in an Animal Model

Abstract: The Osmanthus fragrans flower, a popular herb in Eastern countries, contains several antioxidant compounds. Ben Cao Gang Mu, traditional Chinese medical literature, describes the usefulness of these flowers for phlegm and stasis reduction, arrest of dysentery with blood in the bowel, and stomachache and diarrhea treatment. However, modern evidence regarding the therapeutic efficacy of these flowers is limited. This study was aimed at assessing the antioxidative effects of the ethanol extract of O. fragrans flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 52 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…The results of a study performed by Park et al demonstrated that high amounts of oxidative stress occur before many of the common characteristics of allergic airway diseases including inflammation [ 79 ]. Epithelial shedding, smooth muscle contractions in the airway, and mucus hypersecretion all contribute to airway hyperresponsiveness induced by oxidative stress [ 80 ]. Accordingly, researchers have been able to mitigate the development of certain asthmatic symptoms via antioxidant treatments [ 79 ].…”
Section: Redox Mechanisms In the Pathogenesis Of Asthmamentioning
confidence: 99%
“…The results of a study performed by Park et al demonstrated that high amounts of oxidative stress occur before many of the common characteristics of allergic airway diseases including inflammation [ 79 ]. Epithelial shedding, smooth muscle contractions in the airway, and mucus hypersecretion all contribute to airway hyperresponsiveness induced by oxidative stress [ 80 ]. Accordingly, researchers have been able to mitigate the development of certain asthmatic symptoms via antioxidant treatments [ 79 ].…”
Section: Redox Mechanisms In the Pathogenesis Of Asthmamentioning
confidence: 99%
“…Lour., a plant belonging to the Oleaceae family, is widely distributed in Asia, especially in the south and middle of China . Osmanthus fragrans flowers have been demonstrated to attenuate inflammation (Hung et al, 2013;Huang et al, 2015), possess antioxidant activity (Wu et al, 2009;Xiong et al, 2014;Jiang et al, 2015), protect against ageing (Xiong et al, 2016) and inhibit melanogenesis (Wu et al, 2009). With these benefits, the O. fragrans flowers are used as folk medicine and as additive for teas, beverages and foods, such as pastry, paste, vinegar and liqueurs , and the essential oil of the flowers is used for perfumes, flavours and aromatherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Allergic asthma is a chronic airway inflammatory disease in which many immune regulatory cells within the immune system work together with epithelial cells to cause smooth muscle contraction, enhance airway hyper-reactivity (AHR), increase mucus secretion and stimulate bronchospasm. Non-allergic asthma often develops later in life and, per its definition, has neither immunoglobulin E (IgE) reactivity to allergens nor any obvious involvement of the adaptive immune system, such as type 2 helper T cells (Th2 cells) (1,2). Allergic asthma is more prevalent than non-allergic asthma.…”
Section: Introductionmentioning
confidence: 99%